The enigmatic pattern of long‐distance dispersal of minute freshwater gastropods (Caenogastropoda, Truncatelloidea, Tateidae) across the South Pacific. (22nd June 2016) - Zielske, Susan; Ponder, Winston F.; Haase, Martin
Abstract: Aim: Tateid freshwater gastropods have an enigmatic distribution in the South Pacific (SP) region. We reconstructed their diversification and dispersal pathways and estimated a timeframe for their radiations. Location: New Caledonia, Vanuatu, Fiji, the Austral Islands, further species from Sulawesi, Australia, New Zealand and Lord Howe Island. Methods: Bayesian and maximum likelihood methods were used to calculate dated phylogenies based on two mitochondrial and three nuclear gene fragments, test hypotheses and perform ancestral range reconstructions. We compared two calibration strategies based on the COI substitution rate and two sets of island ages selected (1) independent of the ancestral range reconstruction and (2) using information from the latter. Results: The common ancestor of the SP Tateidae occurred in Australia. Its descendents colonized Sulawesi and Lord Howe Island and gave rise to the radiations on New Caledonia and New Zealand. The more remote archipelagos harbouring the genus Fluviopupa Pilsbry, 1911 were colonized out of New Zealand. Fluviopupa evolved on the Austral Islands and colonized the archipelago against the progression rule from east to west. Vanuatu was colonized twice independently from the Austral Islands and served as hub for dispersal events to Fiji and Lord Howe Island. The second strategy for calibrating the time trees resulted in considerable younger colonization estimates, was generally well in accordance with the geological record and required fewer ad hoc hypotheses to explain the diversification and dispersal pattern. Main conclusions: Our analyses of the evolutionary history of Tateidae across the SP revealed several enigmatic aspects not in accordance with the dominant pattern published for other taxa. In particular, the complex westward dispersal pathways of Fluviopupa, which originated on the Austral Islands but had an ancestor in New Zealand, are unique. Geographical distance was not an appropriate predictor of relationships.